Mapping of Aglets into E-speak - Andreas, Schmid (2008)
This project proposes and implements a system for seamless integration of HP E-speak E-services and IBM Aglet mobile agent applications onto a common platform. And it conducts a systematic comparative study between E-speak, Aglets, related technologies, and E-Commerce requirements.